Analisis Efektifitas Taktik Offense Tim Putra Jawa Timur Pada Kejuaraan Nasional Bola Tangan Tahun 2022 di Jakarta - Firsta Farrel Berlyano (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2024)
Handball is a sport played with one or two hands, involving two teams attempting to score goals by throwing a ball into the opponent's goal defended by several defending players and a goalkeeper. Each team consists of 7 players, with 6 players serving as attackers and defenders, and 1 goalkeeper. The matches are typically conducted indoors on a field measuring 40 x 20 meters, featuring two goals measuring three meters in height and two meters in width. In handball, each athlete is expected to master various fundamental techniques, which serve as crucial factors for success. This research adopts a non-experimental approach with a quantitative descriptive method, aiming to clarify research results. The sample collection employs a purposive technique, analyzing offensive tactics in 4 matches based on 5 tactics created by the coach of the East Java handball team. Data collection is conducted through video documentation, analyzing a research form containing tables for each success and failure system. The research findings reveal the success and failure rates of teams in utilizing offensive tactics, with East Java vs West Kalimantan achieving a success rate of 59.42% and a failure rate of 40.58%, East Java vs Riau Islands with a success rate of 73.58% and a failure rate of 26.42%, East Java vs North Kalimantan with a success rate of 54.72% and a failure rate of 45.28%, and East Java vs DKI Jakarta with a success rate of 48.72% and a failure rate of 51.28%. The analysis uses the formula r= ∑x X 100% to calculate the average success and failure of the total systems that succeeded and failed in each match.